Ruteng Diocesan Church as An Ecological Community: Practicing Ecopastoral Amid an Ecological Crisis - Jean Loustar Jewadut; Alexander Jebadu; Ferdinandus Sebho (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
The ecological crisis threatens human life. In the face of the ecological crisis, the Church is called to be sensitive and involved in efforts to save the environment. Practicing ecopastoral is a form of the Church's involvement in saving the environment. Conducted by literature research, this article seeks to explain the ecopastoral praxis that can be applied by the Ruteng Diocesan Church as an ecological community. In order to raise the awareness of the people about ecopastoral as a joint movement, the Ruteng Diocese Church needs to integrate the local wisdom of the Manggaraians into the ecopastoral praxis. In practice, the Ruteng Diocese Church can live the ecological liturgy, ecological kerygma, and ecological diakonia as an important content of ecopastoral praxis.